Giant Chemo-Resistive Response of POSS Nano-Spacers in PS- and PMMA-Based Quantum Resistive Vapour Sensors (vQRS) Used for Cancer Biomarker Analysis - Abhishek Sachan; Mickaël Castro; Veena Choudhary; Jean-François Feller (Chemosensors)
The detection of volatile organic compound (VOC) biomarkers from the volatolome for the anticipated diagnosis of severe diseases such as cancers is made difficult due to the presence of high quantities of H2O in the collected samples. It has been shown that water molecules tend to compete or combine themselves with analytes, which requires either their removal or the development of more sensitive and discriminant sensors. In this later prospect, a positive effect of poly(hedral oligomeric silsesquioxanes) (POSS) is sought out to enhance the sensitivity of carbon nanotube-based quantum resistive vapour sensors (vQRS). POSS, once copolymerized with methyl methacrylate or styrene, can be used as nano-spacers amplifying the disconnection of the nano-junctions due to swelling of the polymer upon the diffusion of VOC. The amplitude of this phenomenon, which is at the origin of the chemo-resistive behaviour of vQRS, was compared with that of homologue transducers made of poly(styrene) (PS) and poly(methyl methacrylate) (PMMA)-coated carbon nanotube (CNT) random networks. The presence of POSS in PS-based sensors has enhanced their sensitivity by 213 times for toluene, by 268 times for acetone, by 4 times for ethanol, and by 187 times for cyclohexane. Similarly, the presence of POSS in PMMA chains increases the sensitivity of sensors to cyclohexane by 10 times, to ethanol by 45 times, to toluene by 244 times, and to acetone and butanone by 4 times. All transducers were made by spray layer by layer (sLbL) to obtain a hierarchically structured conducting architecture. The transducers’ surface was characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM) to observe the CNT coating and dispersion level in the matrix. All sensors were tested with twenty-one VOC part of lung and skin cancer biomarkers by using a dynamic vapour analysis (DVA). The vQRS based on POSS copolymers demonstrated much larger chemo-resistive responses (AR) than the sensors based only on pure polymers and were found to be very selective towards cyclohexane and hexene-1. The PMMA-co-POSS/CNT sensor was able to detect down to 12 ppm of VOC with a very high signal-to-noise ratio (SNR) and to discriminate six VOC among them all with a PCA (principal component analysis) projection.